Endoscopic Vs. Microscopic Discectomy for Single Level Lumber Prolaps Disc Patients - Zia-Ur-Rehman, Muhammad Ibrahim, (Pakistan Journal of Medical & Health Sciences, 2023)
Objective: An endoscopic discectomy and a microdiscectomy for lumbar spine disc disease were compared in a randomized controlled trial. Material and Methods: This randomized controlled experiment study conducted at the tertiary care hospital of KPK from Jan 2021 to Jan 2022. The study comprised 40 patients suffering from low back discomfort that travels down their legs and who have prolapsed intervertebral discs at the L5-S1 and L4-L5 levels, as shown on magnetic resonance imaging (MRI). They varied in age from 12 to 64. Endoscopic/microscopic discectomy with fluoroscopic guidance was conducted while the patient was laying on his or her back under a general anesthetic. All patients were monitored who spending two hours in the recovery room after surgery before being transferred to the ward. All patients were clinically followed up for a year using the Oswestry disability index (ODI). Results: There were 22(55%) male patients and 18(45%) female patients, ranging in age from 12 to 64. On average, the patients were 52.5 years old. Thirteen (32.5%) and 27(67.5%) patients had prolapsed discs at the L4-L5 and L5-S1 levels. Patients in the endoscopic and microscopic discectomy groups both improved significantly in their analog visual ratings after surgery. Despite this, A less amount of postoperative pain medication was needed, a shorter length of stay in the hospital, and quicker mobility for the endoscopic discectomy group compared to the microscopic group. Conclusion: Both endoscopic and microdiscectomy are safe and equally effective procedures. Each of them is capable of relieving. Nonetheless, early mobility and decreased postoperative discomfort were advantages of the endoscopic discectomy. Keywords: Endoscopic Discectomy, Microscopic Discectomy, Lumbar Prolapse Disc, spinal surgery, Minimally invasive surgery